PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA APARATUR SIPIL NEGARA DINAS PERTANIAN KABUPATEN KEPULAUAN SANGIHE - KATAMANG, ALFRIANTO FREDRIK; TULUSAN, FEMMY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: This study aims to determine and analyze the magnitude of the influence of Human ResourceCompetence on the Performance of Civil State Apparatus in the Department of Agriculture of SangiheIslands Regency. The method that writer use in this research is quantitative method, is research method basedon philosophy of positivism, used for researcher at certain population or sample. Sampling technique used israndom sample technique from research at Agricultural Service of Regency of Sangihe Islands as much 30people. Data analysis techniques used are simple linear regression analysis and simple correlation analysis.Based on the analysis of Correlation Coefficient (r) = 0.812 or 85.9% while the coefficient of determination(rÂ²) = 0.738 or 73.8%. With these results can be explained that the variation of performance changes is alsoinfluenced by variations of competence variables change and the remaining 26.2% influenced by otherfactors. Based on the results of the above research, the hypothesis presented can be accepted. This is indicatedby the amount of contribution factor competence to the performance factor. Based on the results ofsignificant tests obtained Fcount = 14.105 at a significant level of 0.05 with degrees of freedom (df) = n - 2 =28, then Ftabel 4.20. From the data it is obtained that Fcount is greater than Ftable where Fhitung 14.105>4.20. Then Ha accepted and Ho rejected. This proves that there is a significant amount of influence betweenthe Competence of Human Resources on the Performance of Civil State Apparatus in the Agriculture Serviceof the Regency of Sangihe IslandsKeywords: Human Resource Competency, Performance of Civil State Apparatus